The family Lecithoceridae (Lepidoptera, Gelechioidea) from Bioko Island (Equatorial Guinea), with descriptions of five new species - Park, Kyu-Tek; Karisch, Timm (Zootaxa, 2021)
Five new species belonging to the subfamily Torodorinae of Lecithoceridae are described from Bioko Island (Equatorial Guinea), based on specimens which were collected during a short expedition on the island by the second author in 1994. The new species are three species of the genus Thubdora Park, 2018 (T. biocoica sp. nov., T. vernaculella sp. nov., and T. angustiala sp. nov.), and a new species of Ptilothyris Walsingham, 1891and Dragmatucha Meyrick, 1908 respectively (Ptylothyris ruicheensis sp. nov.; and Dragmatucha vulcaniella sp. nov.). In addition, Thubdora bilobella Park, 2018 is reported for the first time from Equatorial Guinea. Images for adults and the genitalia of all species are given.